Reduksi Miskonsepsi Siswa pada Mata Pelajaran PAI di SMPN 5 Jombang - Umi Sholihatin Nisa’; Kurroti A’yun (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
This research was conducted to identify the types of misconceptions that commonly occur in students, identify the factors that influence the occurrence of misconceptions, and identify effective teaching strategies for reducing student misconceptions. This research uses mixed methods, which involve both quantitative and qualitative approaches. The research sample consisted of eighth-grade students at SMPN 5 Jombang. Data was collected through a misconception test, which consisted of questions based on the concept of PAI, class observations, and interviews with students and teachers of PAI. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through thematic analysis. The results showed that there were several types of misconceptions that were common among students, such as misconceptions about worship, aqidah, and religious history. Factors that influence the occurrence of misconceptions include a lack of understanding of basic concepts, the use of less effective learning media, and the influence of the social environment. In addition, this study also identified several effective teaching strategies for reducing students' misconceptions, such as the use of constructivist approaches to learning, interactive learning media, and group discussions. The findings of this study make an important contribution to improving the quality of PAI learning at SMPN 5 Jombang and can also be adopted by other educational institutions. PAI teachers can use the results of this study as a guide in designing effective teaching strategies to reduce students' misconceptions. By reducing misconceptions, it is hoped that students will have a better understanding of PAI subjects, thereby creating a more effective learning environment and supporting the development of students' understanding of religion.